2022
DOI: 10.15698/cst2022.04.266
|View full text |Cite
|
Sign up to set email alerts
|

COX4-1 promotes mitochondrial supercomplex assembly and limits reactive oxide species production in radioresistant GBM

Abstract: Glioblastoma (GBM) is a fatal disease with recurrences often associated with radioresistance. Although often effective at treating newly diagnosed GBM, increasing evidence suggests that radiotherapy-induced alterations in tumor metabolism promote GBM recurrence and aggressiveness. Using isogenic radiosensitive and radioresistant GBM cell lines and patient-derived xenolines, we found that acquired radioresistance is associated with a shift from a glycolytic metabolism to a more oxidative metabolism marked by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…We saw significant upregulation of both nuclear (Cox4i1, Cox5a, Cox5b, Cox6c, Cox7a, Cox7c, Cox8a) and mitochondrial (mt-Co1, mt-Co2, mt-Co3) genes encoding for the 13 subunits of cytochrome c oxidase in the electron transport chain, the key regulator of oxidative phosphorylation 104,105 . More specifically, increases in COX4I1 isoforms are implicated in poorer prognosis, supercomplex formation, increased tumor growth and metastases, and radioresistance [106][107][108] . Therefore, through upregulation of cytochrome c oxidase subunits, especially Cox4i1, ASCL1 increases the efficiency of oxidative phosphorylation and, ultimately, confers a GSC phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…We saw significant upregulation of both nuclear (Cox4i1, Cox5a, Cox5b, Cox6c, Cox7a, Cox7c, Cox8a) and mitochondrial (mt-Co1, mt-Co2, mt-Co3) genes encoding for the 13 subunits of cytochrome c oxidase in the electron transport chain, the key regulator of oxidative phosphorylation 104,105 . More specifically, increases in COX4I1 isoforms are implicated in poorer prognosis, supercomplex formation, increased tumor growth and metastases, and radioresistance [106][107][108] . Therefore, through upregulation of cytochrome c oxidase subunits, especially Cox4i1, ASCL1 increases the efficiency of oxidative phosphorylation and, ultimately, confers a GSC phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…HIF1 activates the components of complex IV through the expression of the cytochrome-c-oxidase (COX) subunit 4-2 (COX4-2) isoform and the mitochondrial protease LON, which degrades COX4-1. Then, COX4-2 substitutes for COX4-1 in cytochrome c oxidase (complex IV), resulting in a more efficient electron transfer to oxygen without increasing ROS levels [194,198], as COX4-1 expression correlates with elevated complex IV activity and increased ROS production [199]. COX4-1 is involved in the formation of mitochondrial supercomplexes containing CTE complex IV, thus promoting an increased rate of respiration and an OXPHOS phenotype in radioresistant cells [199].…”
Section: Role Of Hif1 In Cell Metabolismmentioning
confidence: 99%
“…Then, COX4-2 substitutes for COX4-1 in cytochrome c oxidase (complex IV), resulting in a more efficient electron transfer to oxygen without increasing ROS levels [194,198], as COX4-1 expression correlates with elevated complex IV activity and increased ROS production [199]. COX4-1 is involved in the formation of mitochondrial supercomplexes containing CTE complex IV, thus promoting an increased rate of respiration and an OXPHOS phenotype in radioresistant cells [199]. Oliva et al reported a strong association of COX4-1 levels with poor prognosis in cancer patients, whereas higher COX4-2 concentrations were not correlated in such a way [200].…”
Section: Role Of Hif1 In Cell Metabolismmentioning
confidence: 99%
“…Mitochondria fractions were prepared as previously described [28,[34][35][36]. The activity of ETC complexes and citrate synthase was measured in mitochondrial extracts, as previously described [37].…”
Section: Etc Complexes and Citrate Synthase Activity Assaymentioning
confidence: 99%